Anansi the spider : a tale from the Ashanti - McDermott, Gerald (New York : Scholastic, 1972)
This is a tale about how mischievous Anansi and his six brave sons helped place the moon in the sky!
This book won a Caldecott Honor Award
Keywords: Folktales; Spiders--Fiction.; Children stories